Inhibition of insulin-like growth factors increases production of CXCL9/10 by macrophages and fibroblasts and facilitates CD8+ cytotoxic T cell recruitment to pancreatic tumours - Freeman, Patrick; Bellomo, Gaia; Ireland, Lucy; Abudula, Maidinaimu; Luckett, Teifion; Oberst, Michael; Stafferton, Ruth; Ghaneh, Paula; Halloran, Chris; Schmid, Michael C.; Mielgo, Ainhoa (Frontiers in Immunology, 2024)
Pancreatic ductal adenocarcinoma is a highly lethal malignancy with an urgent unmet clinical need for new therapies. In this study we demonstrate that therapeutic inhibition of the IGF signalling axis promotes the accumulation of CD8 + cytotoxic T cells within the tumour microenvironment of pancreatic tumours. Mechanistically, we show that IGF blockade promotes macrophage and fibroblast production of the chemokines CXCL9/CXCL10 to facilitate CD8+T cell recruitment towards the pancreatic tumour. We show that IGF inhibition leads to increased STAT1 transcriptional activity, correlating with a downregulation of the AKT/STAT3 signalling axis, in turn promoting Cxcl9/Cxcl10 gene transcription. We also demonstrate that our findings translate into the human setting. PDAC tumours are frequently described as "immunologically cold", therefore bolstering CD8 + T cell recruitment to PDAC tumours through IGF inhibition may serve to improve the efficacy of immune checkpoint inhibitors .